(untitled) (Conference Zone, 2022)
In this article, the appearance of the literary language inherent in a certain sphere of social life, a certain colloquial situation is considered a style of speech. Words are divided into stylistically peculiar and stylistically neutral words according to the sign of specificity – non-specificity of speech. Words that apply only within the framework of a particular style of speech are stylistically peculiar words, words that do not have such a feature are called stylistically uncharacteristic or neutral words. Development of speech compensations of pupils of the 8th grade through text types. The text is the appearance of speech, and in terms of its function is a complete speech integrity. Each text has a complex structure and content, and opinions and comments are made about it as an example of oral and written creativity